Regurgitation in healthy and non healthy infants - Cavallo Luciano; Raimondi Francesco; Riezzo Giuseppe; Indrio Flavia; Francavilla Ruggiero (BMC, 2009)
Abstract Uncomplicate regurgitation in otherwise healthy infants is not a disease. It consists of milk flow from mouth during or after feeding. Common causes include overfeeding, air swallowed during feeding, crying or coughing; physical exam is normal and weight gain is adequate. History and physical exam are diagnostic, and conservative therapy is recommended. Pathologic gastroesophageal reflux or gastroesophageal reflux disease refers to infants with regurgitation and vomiting associated with poor weight gain, respiratory symptoms, esophagitis. Reflux episodes occur most often during transient relaxations of the lower esophageal sphincter unaccompanied by swallowing, which permit gastric content to flow into the esophagus. A minor proportion of reflux episodes occurs when the lower esophageal sphincter fails to increase pressure during a sudden increase in intraabdominal pressure or when lower esophageal sphincter resting pressure is chronically reduced. Alterations in several protective mechanisms allow physiologic reflux to become gastroesophageal reflux disease; diagnostic approach is both clinical and instrumental: radiological series are useful to exclude anatomic abnormalities; pH-testing evaluates the quantity, frequency and duration of the acid reflux episodes; endoscopy and biopsy are performed in the case of esophagitis. Therapy with H2 receptor antagonists and proton pump inhibitors are suggested.